Pengetahuan, persepsi, dan sikap masyarakat terhadap inisiasi pembukaan jalur tracking di Desa Komodo, Nusa Tenggara Timur - Ni Made Tasyarani; Nadila Salsadila Hidayat; Zahra Salsabila Rosmaitsa; Lutfiana Purwatiningsih; Muhammad Fahmi Alfachri; Desti Mutiara Putri; Eneng Nunuz Rohmatullayaly (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2023)
Komodo Village on Komodo Island is part of the Komodo National Park area, which is inhabited by a community known as the Ata Modo. The government's development of Komodo Village into a tourist village is responded to positively by the local community in various ways, including homestay services, boat taxis, naturalist guides and initiating the opening of tracking routes in the village. Therefore, it is necessary to conduct research regarding the perceptions, knowledge, and attitudes toward the planned activity. This study used a semi-structured interview method using a questionnaire. The sample of this research is the Komodo Village’s community, namely as many as 81 heads of families covering 5 hamlets. Most of the people in Komodo Village already know about the existence of the tracking route (85%) and agree with the opening of the route, namely 46% (strongly agree) and 44% (agree). In general, the community presumes they will gain benefit economically and socio-culturally from the official opening of the tracking route. However, to continue to protect the biodiversity on Komodo Island and build sustainable ecotourism, it is necessary to study and determine regulations for tourism activities on the tracking route by involving the community.